Applying the Method for Evaluation of Motivational Aspects on Karuchā Ships Invaders Educational Game with Brazilian Students of Japanese - Marciano, Juvane Nunes; Miranda, Erica Esteves Cunha de; Miranda, Leonardo Cunha de (Anais do Workshop de Informática na Escola (WIE); 2014: Anais do XX Workshop de Informática na Escola, 2014)
The increasing use of educational games in several learning contexts is noticed, and to reinforce this growth, it is very important to evaluate these tools in several of their aspects. An important aspect is the influence this kind of tool exercises in the learning process. This paper presents the evaluation of motivational aspects of Karuchā Ships Invaders educational game, through a method developed earlier by the authors, demonstrating that these aspects influence positively on the user's will to continue the learning and practice of Japanese language. The study was applied with Brazilian students of Japanese, and the results show that Karuchā Ships Invaders is a good educational tool for Japanese language learning.